Analisis Desain Formulir Informed Consent Ditinjau dari Aspek Anatomi, Isi, dan Fisik di UPTD Puskesmas - I Indarwati; Rosita Devi Anggraeni; W Wahyuni (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
The provision of health services at the Polokarto Health Center some medical procedures need an informed consent form to provide protection to patients and doctors from malpractice. Based on the preliminary study at the UPTD Polokarto Health Center, there is already an informed consent sheet but there are still elements that have not been entered.Â The purpose of this study is to analyze the Informed Consent form in terms of anatomical, content, and physical aspects at the UPTD Polokarto Health Center. Descriptive type of research with a cross-sectional approach. Research instruments with observation guidelines, interviews. Research data analysis is carried out by collecting, editing, designing forms, and presenting data. The results of observations seen from the anatomical aspects of the heading and revision numbers and instructions have not been included on the Informed Consent form. Aspects of the contents of the Informed Consent form have not listed the type of information and phone number items. The physical aspects of the Informed Consent form still use 70 grams of HVS paper. Some conclusions that must be included on the informed consent form are the revision number, instructions, type of information and telephone number.